Contested centenary: remembering the May Fourth movement in the PRC and across Chinese communities - van Dongen, Els (Asia Research Institute, 2022)
History is no small matter in the People’s Republic of China (PRC). Many readers are probably familiar with the historical narrative of the so-called ‘century of humiliation’ that commenced with the First Opium War from 1839 to 1842. This relevance of history in China goes beyond a mere case of ‘using the past to serve the present’, however: long before the ascent of Mao Zedong, it was believed that one could ‘know the future in the mirror of the past’ (jianwang zhilai). The writing of history was about disclosing the ideal moral order that had been realised during a past Golden Age.